Monitoring Pressure and Saturation Changes in a Clastic Reservoir from Time-lapse Seismic Data Using the Extended Elastic Impedance Method - Shevchenko, Sergey (Curtin University, 2023)
The Extended Elastic Impedance (EEI) concept has been used by the oil industry primarily for lithology and fluid prediction in exploration and development projects. We present a method of reservoir monitoring that identifies and maps changes in pressure and saturation in a producing reservoir by applying EEI to time-lapse seismic data. The method uses time-lapse seismic difference data rotated to specific EEI ? angles which are optimised for the changes expected in a given reservoir.